Alternative Development in Latin America as a Counter Hegemony to Neoliberalism - Setiyaningsih, Dewi; Windiani, Reni; Hasibuan, Eka Maria (Jurnal Ilmiah Widya Sosiopolitika, 2024)
Latin America has an interesting economic development dynamic. As an effort to get out from western imperialism, these countries are aggressively implementing an alternative economic system called Import Substitution Industrialization (ISI). However, this system did not last long and led to a crisis so that countries in Latin America inevitably adopted neoliberal economics. However, neoliberal development has created inequality between the people and  few elites. In such a situation, many countries in Latin America are trying to formulate alternative development recipes in order to get out of economic neoliberalism which has a negative impact on their social and political order. This paper will try to analyze development alternatives in Latin America using the counter hegemony concept developed by Antonio Gramsci. As a case study, this paper takes two examples of Latin American countries that are seeking development alternatives, namely Brazil and Venezuela. Even though they are both against the hegemony of neoliberal development, each of them has different patterns, where Brazil is more compromising, while Venezuela is more radically revolutionary. This difference also causes the success or failure of alternative development in each of these countries.